A sedimentary record from the Makarov Basin, Arctic Ocean, reveals changing middle to Late Pleistocene glaciation patterns. (15th October 2021) - Xiao, Wenshen; Polyak, Leonid; Wang, Rujian; Not, Christelle; Dong, Linsen; Liu, Yanguang; Ma, Tong; Zhang, Taoliang
Abstract: Sediment core ARC5-ICE6 from the Makarov Basin was used to reconstruct circum-Arctic glaciation and surface-ocean circulation history for the Middle to Late Pleistocene, ∼0.5–0.7 Ma. Sedimentary proxies include elemental composition, coarse grain content, clay mineralogy, and radiogenic isotopes (Sr-Nd-Pb). Earlier studied records from the central Arctic Ocean were compared with ICE6 for a broader paleoceanographic context. Results indicate predominant sediment delivery from the Eurasian shelves and glaciated mainland with intermittent glacial inputs from North America. Low proxy variability prior to Marine Isotope Stage (MIS) 6 (∼0.2 Ma) suggests persistent sediment transport by sea ice via the Transpolar Drift and limited glaciation at the Eurasian margin. Since MIS 6, sediment inputs and provenance exhibit large shifts between glacial- and interglacial-type environments. The overall northern Eurasian Ice Sheet (EAIS) expansion was possibly related to climatic cooling and growth of a perennial sea ice in the Arctic Ocean. Provenance indicators from MIS 6, 5b and 4/3 reflect EAIS expansions followed by deglacial meltwater discharge from west Siberia. This provenance indicates a strong cyclonic circulation in the Arctic Ocean characterized by a significantly eastward-extended Transpolar Drift. Different glaciogenic sourcing and attendant circulation are proposed for several events within MIS 5 and 3, where proxies indicate increased sediment inputs from North America rather than Eurasian ice sheets. Overall limited glacial influence inferred for MIS 3 is consistent with relatively high sea level reconstructed for this interstadial. The Last Glacial Maximum is barely identifiable in the ICE6 record due to low glacial inputs and/or depositional hiatus. Highlights: Predominant sediment delivery from the Eurasian shelves to the southern Makarov Basin during the mid-late Pleistocene. Intensified glaciation on Eurasian continent since MIS 6 and heterogeneous development of the ice sheets. Strong cyclonic circulation during intensive glacial/stadials MIS 6, 5b and 4/3.